Nasolabial anthropometry using 3D computed tomography scan reconstruction: baseline study for nasolabial correction in Indonesian children with cleft lip and palate - Erli Sarilita; Harry Galuh Nugraha; Nani Murniati; Endang Sjamsudin; Harmas Yazid Yusuf (Universidad de Concepción., 2024)
Background: The normal nasolabial structure of infants and chil-dren from East Asian, specifically Indonesian, descent groups has been less explored in the literature. This anthropometric study is used as a guide in lip repair in patients with clefts. This retrospective study used archived CT images from the Indonesian population. Materials and Methods: Computed tomography records of children under 5 years of age were extracted from a provincial hospital. The images were then filtered based on the inclusion and exclusion criteria and then the 2D slices were reconstructed using the open source software Invesalius. Twenty-five variable nasolabial parameters of the nasolabial structure were then measured in the 3D rendering mode. Images with craniofacial dysmorphism or cannulas that passed over the nasolabial structure were excluded. Results were summarized using descriptive statistics. Results: Fourteen of 128 CT images were included in this study. The samples were divided into two age groups: 0-12 months and 25-54 months. There were moderate to strong, positive correlations between age and all nasolabial variables, which were statistically significant (p<0.05) except for nasal length, nares circumference, columella width, superior philtrum width, philtrum column height, and cutaneous upper lip height. Conclusions: This study described anthropometric measurements of normal nasolabial structures as a reference point for lip correction surgery. However, to obtain more accurate anthropometric guidelines, further studies with larger sample sizes are desirable. Although surgical repair of the lip is usually performed within the first year of life, some cases of surgery are performed after infancy.